A review on Herbal Anti-Diabetic Formulations and their Importance in Health Sector - Lakavath Sunil Kumar; B Baba Ismail; L Bola Vaishnavi; K Hanshika; K Divya (Oriental Journal Of Chemistry, 2026)
Diabetes mellitus, a chronic metabolic disorder characterized by high blood sugar, is rising globally and can lead to severe complications like heart disease, kidney damage, and nerve disorders. Alongside conventional treatments, herbal remedies are gaining attention for their affordability and minimal side effects. This review explores the role of traditional herbs and commercial formulations in managing diabetes, combining scientific evidence with traditional knowledge. Key herbs like fenugreek (Trigonella foenum-graecum), bitter melon (Momordica charantia), gymnema (Gymnema sylvestre), and cinnamon (Cinnamomum verum) show promising anti-diabetic effects. They work by boosting insulin secretion, reducing glucose absorption, and combating oxidative stress. Commercial herbal blends often combine these for enhanced benefits. However, challenges remain in standardization and clinical validation. While herbal remedies offer a natural approach to glycemic control, further research is needed to integrate them effectively into modern healthcare. Bridging traditional wisdom with scientific validation could provide safer, complementary options for diabetes management.